Randomized, Placebo-Controlled Prospective Clinical Trial Evaluating the Efficacy of the Assisi Anti-anxiety Device (Calmer Canine) for the Treatment of Canine Separation Anxiety - Pankratz, Katherine; Korman, Judy; Emke, Carrie; Johnson, Brianna; Griffith, Emily H.; Gruen, Margaret E. (Frontiers in Veterinary Science, 2021)
Introduction: Separation anxiety (SA) is among the most common canine behavior disorders and affects quality-of-life for dogs and their owners. Dogs with SA show signs of anxiety during absence or perceived absence of their owners. While psychoactive medications are often helpful for treating SA, dog and human factors may limit their utility. This study explored the efficacy of a pulsed electromagnetic field (PEMF) device for treatment of canine SA. Materials and Methods: In this double-blind randomized placebo-controlled study, a screening questionnaire and baseline video confirmed the diagnosis of SA. Owners treated their dog with the device twice daily for six weeks, completed weekly questionnaires, and noted adverse events. Videos were taken of the dog while alone at weeks four and six. Behaviors were coded and categorized as negative and positive. Questionnaire and video data at weeks four and six were compared to baseline. Results: Forty client-owned dogs with moderate to severe SA completed the study. There were no differences between groups for age, weight, or sex. In owner questionnaires, no difference in behavior or overall score was found between the active and sham groups (p > 0.05). Videos of the active group compared to the sham group showed significant reduction in negative behaviors by week six (p = 0.036) and higher percentage of success at week four (Z = 2.83, p = 0.005), at week six (Z = 1.65, p = 0.098), and across the full study (Z = 1.99, p = 0.047). Adverse events were reported in eight dogs (6 active, 2 sham); all resolved and were unlikely to be related to treatment. Discussion: This study supports the efficacy and safety of this PEMF device for treatment of SA in dogs. Questionnaire results may not be sensitive enough to detect subtle negative behavioral states compared to video, and may not capture other owner observed behavioral changes. A caregiver placebo effect may account for some improvement seen in both groups. Video data appear better for diagnosis and monitoring dogs’ behavior when left alone. Future studies should assess PEMF’s impact on other anxieties or combination of anxiety disorders in dogs.